A Tripartite Amplification Loop Involving the Transcription Factor WRKY75, Salicylic Acid, and Reactive Oxygen Species Accelerates Leaf Senescence. Issue 11 (23rd October 2017) - Guo, Pengru; Li, Zhonghai; Huang, Peixin; Li, Bosheng; Fang, Shuang; Chu, Jinfang; Guo, Hongwei
Abstract : A leaf senescence accelerator involving the transcription factor WRKY75, salicylic acid, and H2 O2 is driven by three interlinking positive feedback loops. Abstract: Leaf senescence is a highly coordinated, complicated process involving the integration of numerous internal and environmental signals. Salicylic acid (SA) and reactive oxygen species (ROS) are two well-defined inducers of leaf senescence whose contents progressively and interdependently increase during leaf senescence via an unknown mechanism. Here, we characterized the transcription factor WRKY75 as a positive regulator of leaf senescence in Arabidopsis thaliana. Knockdown or knockout of WRKY75 delayed age-dependent leaf senescence, while overexpression of WRKY75 accelerated this process. WRKY75 transcription is induced by age, SA, H2 O2, and multiple plant hormones. Meanwhile, WRKY75 promotes SA production by inducing the transcription of SA INDUCTION-DEFICIENT2 ( SID2 ) and suppresses H2 O2 scavenging, partly by repressing the transcription of CATALASE2 ( CAT2 ). Genetic analysis revealed that the mutation of SID2 or an increase in catalase activity rescued the precocious leaf senescence phenotype evoked by WRKY75 overexpression. Based on these results, we propose a tripartite amplification loop model in which WRKY75, SA, and ROS undergo a gradual but self-sustained rise driven by three interlinking positive feedback loops. This tripartite amplification loop provides a molecular framework connecting upstream signals, such as age and plant hormones, to the downstream regulatory network executed by SA- and H2 O2 -responsive transcription factors during leaf senescence.